A Study on Post Occupancy Evaluation (POE) of Student Housing Facilities in Kolej Kediaman Pagoh, Universiti Tun Hussein Onn Malaysia - Ahmad Shafie, Nurul Ashikin; Musa, Mohd Kamaruzaman; Mahyeddin, Mohd Eizzuddin (Progress in Engineering Application and Technology, 2022)
Universities need an advanced development system by providing students with good residential facilities and services, including Universiti Tun Hussein Onn Malaysia (UTHM), which offers residential students on the Pagoh campus. Post Occupancy Evaluation (POE) should be conducted to find out the performance of the college. Therefore, this study aims to identify the performance criteria needed for student housing facilities in Kolej Kediaman Pagoh (KKP) using POE and assess the students’ satisfaction with the performance criteria of student housing facilities in KKP through POE. According to the seven criteria known from the literature review, a survey questionnaire was carried out on 322 samples of students living in Kolej Kediaman Pagoh. The respondents’ target was UTHM students who live in student housing provided by UTHM, which were KKP 1, KKP 2, and KKP 3. The sampling method used in this study was a non-probability method, the convenience sampling method. This study analyses the frequency, descriptive, and Pearson correlation coefficient analysis using Statistical Package for the Social Science (SPSS). The results show students’ satisfaction with the student housing facilities performed well except for the internet and Wi-Fi services, and the rest and sports areas with 174 and 132 respondents dissatisfied with the facilities and services provided. From the frequency and descriptive analysis data, most of the students were satisfied with the room’s ventilation and furniture provided. Next, there is a significant correlation between genders with four performance criteria; proximity to essential facilities, cleaning and maintenance, security and safety, and privacy and territory. The interpretation is very weakly positive. From this study, the facility manager can determine students’ satisfaction and further improve the needs and comfort of student housing facilities in Kolej Kediaman Pagoh.